Pengaruh Profitabilitas, Kebijakan Dividen Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Ni Wayan Dian Suarini; Ni Wayan Yuniasih (UNHI Press, 2023)
The value of the company is very influential on the interest of investors to want to invest in a company, especially a manufacturing company. The importance of a company's value causes this research to be conducted to find out what factors can cause the value of a company to increase or decrease. In this study, the factors to be studied are Profitability, Dividend Policy and Company Size. Manufacturing companies listed on the Stock Exchange were selected as the study population. The sample used is 129 companies with the financial statement period used from 2018 -2020. The sample determination uses the purposive sampling method which is processed with multiple linear regression analysis techniques. The results show that the value of the company can increase when the company is able to score high profitability. Dividend policy and company size in fact are not able to affect the value of the company.